Modeling and analysis of modulation techniques for broadband power line communications - Ma, Yinghui (2008)
Multipath and impulsive noise effects of the power line channel are the main challenges for broadband power line communications (PLC). The modulation techniques like orthogonal frequency division multiplexing (OFDM) and code division multiple access (CDMA) can provide good performance for PLC systems. In this thesis, the analytical models to analyze the bit error rate (BER) performance of OFDM and CDMA systems under the multipath and impulsive noise effect are developed and verified by using simulations. The optimized parameters of the OFDM and CDMA systems to achieve the optimum performance in a power line channel are studied. Based on the developed models, a comparison is made between the CDMA and OFDM systems. The BER performance and the optimum overall data rate of the CDMA and OFDM systems are analyzed and compared, using the criteria of the same bandwidth occupation, the same transmission power for each user, the same total number of users in the system and the same power line channel.